Corrosion-fatigue crack growth behaviour of wire arc additively manufactured ER70S-6 steel parts in marine environments - Ermakova, Anna; Ganguly, Supriyo; Razavi, Javad; Berto, Filippo; Mehmanparast, Ali (Elsevier, 2022)
A crucial part of the structural integrity assessment of marine structures is the analysis of the fatigue crack growth behaviour of the welded joints in seawater environments, where the cracks often initiate and propagate under corrosion-fatigue loading conditions. In recent years, technological developments have facilitated the fabrication of steel components and structures using additive manufacturing technologies. Among the existing technologies, the Wire Arc Additive Manufacturing (WAAM) technique has proven to offer great potentials for fabrication of large-scale structures. The present study investigates the corrosion-fatigue crack growth (CFCG) behaviour of the WAAM parts fabricated using ER70S-6 low carbon steel wire to assess the suitability of this technology for future marine structures. In this experimental study, the cracking behaviour and test duration in corrosion-fatigue tests were investigated and analysed in conjunction with the microstructural examination of the tested specimens. Moreover, the obtained results were compared with the recommended trends available in BS7910 standard for conventional welded joints and the data available in the literature on widely used offshore structural steel weldments. The CFCG results obtained from this study contribute to the overall knowledge and design requirements for the new optimised functionally graded structures made with WAAM technology for marine applications.